TEACHING BUSINESS PROCESS MANAGEMENT: IMPROVING THE PROCESS OF PROCESS MODELLING COURSE - Hrabala, Martin; Opletalova, Michaela; Tucek, David (Journal of Applied Engineering Science, 2016)
Process approach is a part of many organizations´ management systems. Process oriented organizations focus on value added processes, their management, performance measurement, improvement and automation. However, in many higher education institutions is not process management implemented and its teaching does not always correspond with business needs and practice. This paper deals with the latter side of process management in higher education - course of process management held at Faculty of management and economics of Tomas Bata University in Zlín. The main purpose of the paper is to present the results of the research among Czech universities and their approach to BPM education and a case study of process management course and its improvement at Faculty  of Management and Economics at Tomas Bata University in Zlín. To improve the course, the very aspects of process management such as customer focus or performance measurement were applied. The performed action research is then described in form of the case study.
Keywords: Process modelling; Process improvement; Higher education; Business process management; Active learning